Acute fatty liver of pregnancy: a retrospective study of 32 cases in South China. (November 2014) - Cheng, Na; Xiang, Tianxin; Wu, Xiaoping; Li, Ming; Xie, Yao; Zhang, Lunli
Abstract Objective: To describe 32 cases of acute fatty liver of pregnancy (AFLP) and identify the potential clinical predictors of maternal and fetal outcomes in South China. Methods: Thirty-two cases of AFLP previously treated in the First Affiliated Hospital of Nanchang University in the past 10 years were enrolled in the current study. Results: Sex of fetus and delivery method was the potential clinical predictor of fetal outcome. The main manifestations of AFLP were jaundice (n = 32), nausea and vomiting (n = 28), malaise (n = 25), and ascites (n = 25), and its complications included acute renal failure (n = 26), hepatic encephalopathy (n = 17), infection (n = 10), and postpartum hemorrhage (n = 7). Evidence of fatty changes of liver was demonstrated by B ultrasound and computed tomography (CT). Eighteen patients were recovered due to rapid diagnosis, early termination of pregnancy and supportive treatments. Conclusions: Male sex and vaginal delivery was the risk factor of fetal outcome. Detailed history taking and proper management of potential predictors are important in making the decision of prompt delivery and choosing the appropriate delivery method. Further studies are needed to expand our knowledge on this disease.